Efforts to Improve the Ability to Recognize Hijaiyah Letters through Interactive Game Methods at SD Negeri 095231 Puli Buah - Marwiyah; Purba, Lisnawati; Damanik, Nila Karmila; Ponirin; Musri (Journal of Media and Learning Technology, 2025)
This study aims to improve students' ability to recognize hijaiyah letters through the application of interactive game methods at SD Negeri No. 095231 Puli Buah. The background of this study is based on the low ability of students to recognize hijaiyah letters due to learning methods that tend to be monotonous and less involving fun activities. This study uses a Classroom Action Research approach which is carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of the study were Muslim students in grades 1-6, with a total of 40 participants. Data were collected through hijaiyah letter recognition ability tests, observation sheets, and student response questionnaires. The game methods used include letter card games, hijaiyah puzzles, and interactive letter guessing. The results showed that the application of interactive game methods significantly improved students' ability to recognize hijaiyah letters. The average student score increased from 55 in the pre-test to 85 in the post-test, with the percentage of learning completion reaching 85% at the end of the second cycle. In addition, observations showed that students became more enthusiastic and active in participating in the learning process. The students’ response to this method was very positive, where 90% of students stated that learning through games made it easier for them to memorize and understand the hijaiyah letters. Based on these findings, it can be concluded that the interactive game method is an effective learning strategy to improve the ability to recognize the hijaiyah letters. This study is expected to be a reference for teachers in developing innovative and fun learning methods, especially in Islamic religious education learning in elementary schools.